Co-responsibility plan and shared parenting - Casado-Casado, Belén María (Routledge, 2021)
In this chapter, a study is made of the doctrinal and jurisprudential evolution experienced on the figure of minor custody and other related terms. The social demands and the proposed legal reform show the reality of this problem. The latest judicial rulings on shared custody are worthy of comment, as they consider shared custody to be a general rule. The conceptual analysis that properly requires the margins of each figure and the development and subsequent evolution of measurement in the courts places us in a suitable position to confront and make proposals of de lege ferenda, since it is a clear fact that legal reform should not be long in coming. But the questions raised by the subject are great and it is very difficult to form a solid opinion except from the generality, in a subject in which the individuality of the causes and circumstances is crucial for the adequate protection of the interest of the minor.
Política de acceso abierto tomada de: https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters
Keywords: Trabajo y familia; Familia y enseñanza; Educación de niños; Minor; Shared parenting; Joint plan; Best interest of the child; Co-responsibility